2019
DOI: 10.3390/min10010013
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Talc and Fe-Ti-V Mineralization in the Kletno Deposit (the Śnieżnik Massif, SW Poland)

Abstract: The Kletno deposit in theŚnieżnik Massif (Central Sudetes, SW Poland), mined for Fe, U, Ag, Cu, fluorite, and marble through the ages, developed at the contact of marbles and orthogneiss. Here, we present a new Fe-Ti-V-ore (containing up to 14.07 wt. % Fe, 2.05 wt. % Ti, and 2055 ppm V in bulk rock) and ornamental-to gem-quality talc prospect at the southwest margin of this deposit. This newly documented Fe-Ti-V mineralization is hosted in hornblendites, dolomite veins, and chlorite schists, which, along with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These fluids probably resulted from dehydration during metamorphism (early stage) or magmatic fluids from nearby granitic intrusions (late stage) certainly along from W. Reiidi (Atshan) and El Kharit (Darhib) granitic rocks that are responsible for silica additions 4 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…These fluids probably resulted from dehydration during metamorphism (early stage) or magmatic fluids from nearby granitic intrusions (late stage) certainly along from W. Reiidi (Atshan) and El Kharit (Darhib) granitic rocks that are responsible for silica additions 4 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Talc typically forms from hydrothermal alteration or metamorphism of dolomites and ultrabasic rocks (Evans and Guggenheim, 1988;Schandl et al, 2002;Ali-Bik et al, 2012;Gil et al, 2020), but is rarely reported as a sedimentary mineral (Tosca et al, 2011).…”
Section: Introductionmentioning
confidence: 99%